Detection and variant characterization of lumpy skin disease virus from dairy cattle in India - Bajpai, Manali; Khilari, Ajinkya; Likhitkar, Bhagyashree; Musale, Pankaj; Jadhav, Santoshkumar; Dhanikachalam, Velu; Kakramkar, Payal; Bhave, Kaustubh; Swaminathan, Marimuthu; Joshi, Sachin; Shanmugam, Dhanasekaran (Virus Evolution, 2025)
The spread of a severe and often fatal form of lumpy skin disease (LSD) in cattle and water buffaloes has caused widespread mortality and morbidity of these animals in India. To track and understand the genetic changes occurring in the virus and to enable routine surveillance of the virus, multiplexed polymerase chain reaction (PCR) and sequencing methods were developed and validated in this study. Multiplexed nested PCR for LSD virus (LSDV) detection was optimized using skin lesion swabs and nasal samples collected from symptomatic and asymptomatic animals. For genotyping, overlapping PCRs to amplify the entire LSDV genome were developed and tested on field samples collected from the Maharashtra and Odisha states of India. Analysis of LSDV genomes from 41 field samples collected in 2022 and 2023 revealed the presence of highly conserved novel mutations. Phylogenetic analysis shows that a distinct genotype of LSDV has spread across India, which warrants genomic surveillance of the virus in the coming years to track the evolution and transmission of the virus. The non-invasive sample collection, detection, and genotyping methods described in this study can facilitate large-scale surveillance of LSDV in dairy animals.
Keywords: genotyping by sequencing; lumpy skin disease; multiplexed nested PCR; Oxford Nanopore technology; virus surveillance